PhyGeometry: ORGANizing physiology - Hwee-Ming Cheng; See-Ziau Hoe (Wolters Kluwer Medknow Publications, 2021)
PhyGeometry is a visual learning and teaching aid, combining physiological information into and part of geometric triangles. PhyGeometry is a useful summary picture of key factors that affect or are part of a physiological event or mechanism. PhyGeometry helps to "ORGANize," bring order, beauty, and symmetry into learning and teaching physiology.